Analisis Kesesuaian Instrumen Hedge Konvensional terhadap Prinsip Syarih - Cipto Sembodo (TASAMUH: Jurnal Studi Islam, 2019)
International finance is one of the areas that starts to attract attention of Islamic financial experts. In a more globalized market, Islamic banks need to be more exposed into international market in order to facilitate export-import transactions. Consequently, the Islamic banks are dealing with exchange rate risk higher than earlier. In the conventional counterpart, the risk can be minimized through hedging instruments; thus, gaining a higher level of operational efficiency. In an absence of such instruments, this paper offers possible mechanisms that could be beneficial for further development of so-called “Islamic hedge-mechanism”.One of the offers is how mudharabah or musharakah contract can be used to construct an Islamically acceptable hedge instruments.